Pengaruh Aliran Hukum Positivisme dan Rasa Keadilan di Indonesia - Indriyani, Irma (AHKAM, 2022)
Legal positivism school of thought or Legal Positivism has a strong influence in law enforcement in Indonesia. The method used in this research is a qualitative method with a literature study approach. The results of his study concluded that law enforcement prioritizes the side of legal certainty compared to a sense of justice, this happens because in law enforcement judges pay less attention to other aspects of enforcement such as sociological, psychological, ethical and moral. Therefore, the author proposes a legal reform related to strengthening values religion, Pancasila and progressive law enforcement.